2021
DOI: 10.1007/s00784-021-04096-z
|View full text |Cite
|
Sign up to set email alerts
|

Standardized palpation of the temporalis muscle evoke referred pain and sensations in individuals without TMD

Abstract: Standardized palpation of the temporalis muscle evoke referred pain and sensations in individualswithout TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The evaluation of muscle pain by palpation is therefore a pivotal part of the clinical examination in patients with myalgia. Masuda et al 9,10 . have reported that standardized palpation of the masseter and temporalis muscles can evoke referred pain and sensations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of muscle pain by palpation is therefore a pivotal part of the clinical examination in patients with myalgia. Masuda et al 9,10 . have reported that standardized palpation of the masseter and temporalis muscles can evoke referred pain and sensations.…”
Section: Introductionmentioning
confidence: 99%
“…8 The evaluation of muscle pain by palpation is therefore a pivotal part of the clinical examination in patients with myalgia. Masuda et al 9,10 have reported that standardized palpation of the masseter and temporalis muscles can evoke referred pain and sensations. The degree of pain elicited by palpation is determined by several factors, with the intensity of pressure exerted by the observer as likely the most important.…”
mentioning
confidence: 99%